Prevalence and profile of patients diagnosed with AMI attended in a private emergency service (Research, Society and Development, 2024)
The objective of this study is to describe the prevalence and profile of patients diagnosed with AMI treated at a private emergency care unit. This was a cross-sectional and retrospective study, with secondary data from medical records of patients diagnosed with AMI at a private emergency care unit of a hospital in the city of São Paulo/SP, Brazil. Data were collected using Microsoft Forms. Descriptive and analytical analysis of these patients was then performed. The study sample consisted of 31 patients. The prevalence of patients diagnosed with AMI at the institution was 0.001%. Males, age over 60 years, and white race were predominant. Systemic Arterial Hypertension (SAH) and heart disease were the antecedents presented by most individuals, who in turn did not exercise, had a history of smoking, and approximately 29% consumed alcohol, 33% of which consumed alcohol excessively. Chest pain, radiating to the upper limbs, was the predominant symptom, beginning within one hour of arrival at the service. There was one death without treatment due to cardiopulmonary arrest before the intervention, the other 30 received treatment aimed at AMI. The death rate was 19%. It was concluded that this study expanded knowledge in the field of scientific research regarding acute myocardial infarction, identifying data that can be used as a basis for adaptation and/or creation of institutional protocols aimed at improving the clinical approach in the first care and segments of these patients.